Cholesteryl esters: fueling the fury of prostate cancer - Peck, Barrie; Schulze, Almut (Cell metabolism, 2014)
Tumors display distinct metabolic programs, and altered lipid metabolism is emerging as an important process in cancer. In this issue, Yue et al. (2014) report that aberrant cholesteryl ester accumulation is found in advanced prostate cancers with PTEN loss and PI3K/AKT activation. Importantly, inhibition of cholesterol esterification impaired cancer aggressiveness.